Análise dos conhecimentos para ação docente em argumentação manifestados por uma professora em formação inicial - Ellen Catharina Ponciano Siqueira (2023)
The decontextualized use of experiments and phenomenon observation may create in students a distorted view of what is Science and how it is produced. In order to avoid this distortion, some scholars (Mccomas, 2008; Santos; Maia; Justi, 2020) support presenting science in a humanistic and socially constructed perspective. To achieve that it is necessary to introduce students to inherent practices related to the construction of scientific knowledge, such as argumentation (Jiménez-Aleixandre, 2010). Duschl and Osborne (2002) emphasize the importance of creating an environment favorable to argumentation, and for that, the teacher plays a key role in fomenting and supporting argumentative scenarios in the classroom. In that sense, some researchers demonstrate a need to rethink teacher training in order to make argumentation more effective and frequent in teaching spaces. Thereby, this research was developed in context of the Pedagogical Residence Program, (PRP), a theoretical-practical training program focused on argumentation and chemistry teacher targeted, in a federal university. In the weekly meetings, the teachers debated topics related to argumentation and they were guided to plan didactic sequences based on that approach. One of the teachers from this program stood out for her active role in the activities and in the planned sequences, and for that reason the data analyzed in this research was collected from her steps of planning, practice and reflection. The research aimed to point out what knowledge and how they were mobilized by the teacher during her first years of the graduate course. To achieve this aim, questionnaires and interviews were made with the graduate student and the planning class session and the lessons with its didactic sequence were recorded. The data and documents from the formation were read and analyzed which allowed us to select three main events in the process. The data analysis showed that in several moments the teacher-training student mobilized knowledge to the teaching act and expressed favorable actions to Science teaching including that approach. However, the graduate student had some issues during the process, which indicate that it is not only necessary to mobilize knowledge about argumentation for students in early years of graduation, or introduce them to this approach. The contact must be reflective and guided, in a way that teachers in the formative years develop bigger and more complex experiences with argumentation in the classroom. This research conclusion points to the manifestation of different knowledge about argumentation by the undergraduate student and indicate that such knowledge needs to be linked to other teaching knowledge in the development of teaching practice.